The Association of Power Napping with Obesity and Dietary Habits Among the Age Group of 6-18 Years: Corresponding authors: wanrohani@unisza.edu.my, shanthikrishnasamy@ukm.edu.my - Mustafa, Faheem; Syeda Bisma Aamer; Syeda Momna Ali; Akmal, Iram; Tehreem Akram; Mubashara Akbar; Arooj Gull; Ammara Arshad; Rabiatul Adawiyah Binti Umar; Atika Hashmi; Fatin Hanani Mazri; Shanthi Krishnasamy*; et al. (Progress in Nutrition, 2025)
Obesity, characterized by excessive fat accumulation, is often defined by the WHO using BMI. Power naps, short daytime sleeps of 10 to 90 minutes, impact body metabolism and weight regulation. The aim of this research was to explore the association between power napping and the risk of obesity using anthropometric measurements, waist circumference percentile, BMI percentile, and usual dietary intake to evaluate the risk of obesity-related metabolic conditions. This was a cross-sectional and comparative study conducted among 300 children and young adolescents aged between 6 and 18 years. Anthropometric measurements (weight, height, waist circumference, BMI) were taken according to WHO guidelines. Dietary history was obtained through a 24-hour usual dietary recall and a food frequency questionnaire. The Cronometer tool was used for dietary analysis, and statistical analysis was performed using SPSS 28.0 software. The results showed that 36.30% of power nappers were normal, 2.60% were overweight, while 2.30% were obese. However, 32% of non-nappers were normal, 7.60% were overweight, and 6% were obese. The mean prevalence of overweight and obesity was higher in non-nappers than power nappers, but no significant association was found between them (P > 0.05). Dietary habits were better in power nappers than in non-nappers, with a significant association found (P < 0.05). Interventions for pediatric obesity are limited, and understanding all factors contributing to the risk of obesity is crucial. Although research supports biphasic sleeping patterns, the topic requires further investigation to fully understand its implications. Limitations of this study highlight the need for additional research to validate and expand upon these findings.